A Guide to Nucleic Acid Vaccines in the Prevention and Treatment of Infectious Diseases and Cancers: From Basic Principles to Current Applications - Qin, Furong; Xia, Fan; Chen, Hongli; Cui, Bomiao; Feng, Yun; Zhang, Ping; Chen, Jiao; Luo, Min (Frontiers in Cell and Developmental Biology, 2021)
Faced with the challenges posed by infectious diseases and cancer, nucleic acid vaccines present excellent prospects in clinical applications. Compared with traditional vaccines, nucleic acid vaccines have the characteristics of high efficiency and low cost. Therefore, nucleic acid vaccines have potential advantages in disease prevention and treatment. However, the low immunogenicity and instability of nucleic acid vaccines have limited their development. Therefore, a large number of studies have been conducted to improve their immunogenicity and stability by improving delivery methods, thereby supporting progress and development for clinical applications. This article mainly reviews the advantages, disadvantages, mechanisms, delivery methods, and clinical applications of nucleic acid vaccines.